2017
DOI: 10.3389/fpls.2017.00598
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Hydraulic Architectures of Scots Pine and Sessile Oak at Their Southernmost Distribution Limits

Abstract: Many temperate European tree species have their southernmost distribution limits in the Mediterranean Basin. The projected climatic conditions, particularly an increase in dryness, might induce an altitudinal and latitudinal retreat at their southernmost distribution limit. Therefore, characterizing the morphological and physiological variability of temperate tree species under dry conditions is essential to understand species’ responses to expected climate change. In this study, we compared branch-level hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 87 publications
3
12
0
Order By: Relevance
“…Therefore, the two ring-porous species recorded higher values of K S-MAX than Scots pine since their xylem architecture is better designed for an efficient water transport. Similar results were found in other studies comparing angiosperms and conifers [51]. However, with increasing aridity, sweet chestnut, Scots pine and to a lesser degree oak displayed lower K S-MAX suggesting an acclimation of the xylem.…”
Section: Contrasting Hydraulic Strategies Among the Study Speciessupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the two ring-porous species recorded higher values of K S-MAX than Scots pine since their xylem architecture is better designed for an efficient water transport. Similar results were found in other studies comparing angiosperms and conifers [51]. However, with increasing aridity, sweet chestnut, Scots pine and to a lesser degree oak displayed lower K S-MAX suggesting an acclimation of the xylem.…”
Section: Contrasting Hydraulic Strategies Among the Study Speciessupporting
confidence: 90%
“…These low values of native loss of conductivity found in our study are in disagreement with the ones reported by [72], who found a strong decline in native PLC in a Scots pine population located in the NE Iberian Peninsula. However, a more extensive study assessing the native loss of conductivity across Scots pine stands, located at the southern limit of the species distribution during one of the driest summers in the area, found similar values as ours [51]. Nevertheless, this conservative strategy allows keeping the xylem functional in water transport during several years, since the annual build-up of new xylem tissue just accounts for 15-20% of the total hydraulic conductivity [75].…”
Section: Contrasting Hydraulic Strategies Among the Study Speciessupporting
confidence: 80%
See 1 more Smart Citation
“…Driven by the meteorological conditions, sap flux rates were higher in May–August than in April and September. The sap flux in April and September would be consistent with these 2 months being in the early and late period of annual growth of Scots pine (Martínez‐Sancho, Dorado‐Liñán, Hacke, Seidel, & Menzel, ; Whittet, Cavers, Cottrell, Rosique‐Esplugas, & Ennos, ). May in this year had relatively low precipitation input (~37 mm), which potentially limited the replenishment of root‐zone soil moisture.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding European forests, the economically most important and spatially most abundant tree species of Scots pine ( Pinus sylvestris , L.) and Norway spruce [ Picea abies , (L.) Karst.] are regionally experiencing increased mortality rates (Bigler et al, 2006; Kohler et al, 2010; Lévesque et al, 2013; Rigling et al, 2013; Zang et al, 2014; Huang et al, 2017; Martínez-Sancho et al, 2017; Rehschuh et al, 2017; Buras et al, 2018). But also the widespread European beech ( Fagus sylvatica , L.) is likely to suffer (Scharnweber et al, 2011, 2013; Dulamsuren et al, 2017; Huang et al, 2017; Walentowski et al, 2017) while other abundant species such as oak [ Quercus robur , L. and Quercus petraea , (Matt.)…”
Section: Introductionmentioning
confidence: 99%